“THE EDUCATIONAL SIGNIFICANCE OF DANIEL DEFOE’S ROBINSON CRUSOE: ENLIGHTENMENT IDEALS REFLECTED IN LITERATURE” (Ustozlar uchun, 2026)
This article explores Daniel Defoe’s Robinson Crusoe as a literary work deeply embedded in the intellectual currents of the Enlightenment. It analyzes how the novel, beyond its popular appeal as an adventure story, serves as a powerful educational text. The protagonist's journey, characterized by experiential learning, self-reliance, and moral development, reflects key pedagogical principles advocated by Enlightenment philosophers such as Jean-Jacques Rousseau and John Locke. Through a close literary analysis, the study argues that Robinson Crusoe functions as an educational model that continues to be relevant in the context of modern teaching and human development.